Ahmed Deedat's Theology of Religion: Apologetics through Polemics - Westerlund, David (Journal of Religion in Africa, 2003)
Within Africa, as well as outside the continent, the writings and videocassettes of Ahmed Deedat have been, and still are, most influential. In this article, Deedat's great interest in religious polemics, especially against Christianity, has been interpreted primarily as an apologetical endeavour influenced largely by the marginal and exposed situation of the small minority of Muslims in the strongly Christian-dominated South Africa. Deedat's main task was to provide Muslims with theological tools for defending themselves against the intense missionary strivings of many Christian denominations. He spoke and wrote for the Muslim masses rather than for learned scholars, and the fact that he used English instead of Arabic or some other 'Muslim' language further increased the availability of his writings among, for instance, Muslim minorities in Europe and North America.
free